MODELING OF LIGATURE DISSOLUTION IN COPPER MELT AT SMELTING OF CHROMIC BRONZES AND OPTIMIZATION OF THEIR PRODUCTION PROCESS - F. G. Lovshenko; G. F. Lovshenko; B. B. Hina; I. A. Lozikov (Литьë и металлургия)
The results of modeling and their experimental-industrial test of alloy dissolution in the form of elementary chrome, cast and mechanically doped alloys «copper-chrome» system in copper melt at melting of chrome bronzes are given, the process of their production is optimized.